Some aspects of sustainable mobile infrastructure growth of Bangladesh - Asif, Shahid Muhammad; Khan, Nasif; Mortuza, imtiazul Haque (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.